Surveying the flat circuits at high frequencies with FWM and FDTD - Pham, Ngọc Sơn; Pham, Thành Trung (Journal of Technical Education Science, 2010)
There are various ways to survey the flat circuits at high frequencies. The most popular models are Microstrip Line Model (MLM), Cavity Model (CM) and Full-Wave Model (FWM). Among the above mentioned models, MLM is the least accurate model and unable to use for complex flat models. The CM is more accurate, and also more complex than the MLM. Yet, this model is well fit to the twin antenna with the good results. FWM is a flexible model that we can use for designing single patterns, complex patterns, or multi patterns also…. Therefore, this paper will in this context provide FWM and FDTD (Finite Difference Time Domain) method for surveying this model.